Spatiotemporal Trend Analysis of the Mean Annual Rainfall in Senegal - Lamine Diop; Ansoumana Bodian; Dior Diallo (European Scientific Journal, ESJ, 2016)
The spatiotemporal trends of annual rainfall in Senegal during 1940 - 2013 were investigated using the Mann–Kendall test and Theil–Sen’s slope estimator. Theil and Sen's slope estimator test was used for finding the magnitude of change over a time period. Inverse Weight Distance (IDW) technique in Arc GIS 10.2 was used to investigate spatial patterns of the trends over the entire country. For the period 1940-2013, the results of the analysis showed negative trends in annual rainfall at the whole country except for the Bakel station which exhibits a positive trend but not significant. While for the period 1984 - 2013, all the stations show a positive trend with 07 out of 22 stations exhibiting a significant trend at the 95% confidence interval. The spatial distribution of trend during the period 1940- 2013 showed a significant negative trend in the whole study of area except small areas located at the extreme South Est and West as well as North East and West. The trend magnitude varies between -4.41mm/year to 1.34 mm for the period 1940-2013 with a maximum negative magnitude at the Tambacounda station. For 1984-2013, the trend magnitude is positive for the whole country with values varying between 2.67 mm/year at Goudiry and 12.2 mm/year at Ziguinchor. Magnitudes are greater than 5 mm/year, for stations with significant positive trend.